The relationship of plasma fibrinogen with clinicopathological stages and tumor markers in patients with non-small cell lung cancer. Issue 32 (August 2019) - Bian, Nan-Nan; Shi, Xin-Yu; Qi, Hong-Yu; Hu, Xin; Ge, Yang; An, Guang-Yu; Feng, Guo-Sheng
Abstract : Abstract: Numerous studies have shown that the blood of cancer patients are generally in hypercoagulable statement. The aim of the present research is to study the relationships of plasma fibrinogen (Fbg) levels with clinicopathological stages (CS) and tumor markers of non-small cell lung cancer (NSCLC). Baseline information, plasma Fbg levels, CS, and expression level of tumor markers were collected from medical records retrospectively. Unitary linear regression was used to analyze the relationships between continuous variables and Fbg, and multiple linear regression was used to analyze the relationships between categorical variables and Fbg. National Comprehensive Cancer Network Clinical Practice Guidelines in Oncology (Version 4) for NSCLC were adopted to evaluate CS. A total of 652 NSCLC patients were included. Compared with the females, male patients had higher mean plasma Fbg levels ( P < .001). The later the N stages ( P = .002), M stages ( P = .002), and CS ( P = .001) were, the higher the average plasma Fbg levels were. The levels of squamous cell carcinoma antigen ( P = .001), carbohydrate antigen 125 ( P = .041), and neuron-specific enolase ( P < .001) were positively correlated with plasma Fbg concentration. The plasma level of Fbg in lung adenocarcinoma patients ( P < .001) was the lowest, while that of lung squamous cell carcinoma patients ( P < .001) was the highest in NSCLC patients. The plasma Fbg concentration is related to gender, CS, and tumor markers in patients with NSCLC.